Determinants of induced abortion among women of reproductive age: evidence from the 2013 and 2019 Sierra Leone Demographic and Health Survey - Foday Robert Sesay; Emmanuel Anongeba Anaba; Adom Manu; Ernest Maya; Kwasi Torpey; Richard M. K. Adanu (BMC, 2023)
Abstract Background Worldwide, pregnancy termination due to unintended pregnancy is crucial in maternal health, particularly in settings where abortion laws are restrictive. Presently, there is a paucity of literature on determinants of induced abortion among women of reproductive age in Sierra Leone. The study findings could be used to improve the country's maternal mortality indices and inform health programs and reproductive health policies geared toward tackling induced abortion. Methods We analyzed secondary data from the 2013 and 2019 Sierra Leone Demographic and Health Surveys. The surveys were nationally representative, with weighted samples comprising 16,658 (2013) and 15,574 (2019) women of reproductive age. Descriptive statistics, including frequencies and percentages, were computed, while Chi-square and Binomial Logistics Regression were employed to identify correlates of induced abortion. Results The results showed that a minority (9%) of the participants had induced abortion in both surveys. Abortion was significantly associated with age, marital status, employment status, education, parity, and frequency of listening to the radio and watching television (p < 0.05). For instance, women aged 45-49 years (AOR = 7.91; 95% CI: 5.76-10.87), married women (AOR = 2.52; 95% CI: 1.95-3.26), and working women (AOR = 1.65; 95% CI: 1.45-1.87) had a higher likelihood of induced abortion compared to their counterparts. Moreover, women with primary education (AOR = 1.27; 95% CI:1.11-1.46) and those who watch television once a week (AOR = 1.29; 95% CI: 1.11-1.49) were more likely to terminate a pregnancy. Women with six or more children (AOR = 0.40; 95% CI: 0.31-0.52) were less likely to terminate a pregnancy compared to those with no child. Conclusion The study revealed that a minority of the women had induced abortions. The prevalence of induced abortion did not change over time. Induced abortion was influenced by age, marital status, employment status, education, parity, and exposure to mass media. Therefore, policies and programs to reduce unwanted pregnancies should focus on increasing access to modern contraceptives among women of lower socio-economic status.